2015
DOI: 10.9714/psac.2015.17.3.013
|View full text |Cite
|
Sign up to set email alerts
|

Delamination behaviors of GdBCO CC tapes under different transverse loading conditions

Abstract: In superconducting coil applications particularly in wet wound coils, coated conductor (CC) tapes are subjected to different type of stresses. These include hoop stress acting along the length of the CC tape and the Lorentz force acting perpendicular to the CC tape's surface. Since the latter is commonly associated with delamination problem of multi-layered CC tapes, more understanding and attention on the delamination phenomena induced in the case of coil applications are needed. Difference on the coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…During the anvil test, the stress concentrated along the micro-cracks at the slit edges, affecting the delamination behavior of the superconducting layer side. The same results were also obtained when the superconducting layer was placed facing upward toward the upper anvil listed in table 2 [18].…”
Section: Fractographic Morphologies Of Delamination Sites In CC Tapessupporting
confidence: 72%
See 2 more Smart Citations
“…During the anvil test, the stress concentrated along the micro-cracks at the slit edges, affecting the delamination behavior of the superconducting layer side. The same results were also obtained when the superconducting layer was placed facing upward toward the upper anvil listed in table 2 [18].…”
Section: Fractographic Morphologies Of Delamination Sites In CC Tapessupporting
confidence: 72%
“…In our previous reports, we used a transverse tensile testing frame and anvil test methods, devised to perform systematic delamination testing procedures [16][17][18]. We have found that the electromechanical delamination strength, σ el , significantly increased when smaller-sized anvil was used even when it was done experimentally and numerically simulated [12,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been widely used in recent years to describe the strength properties and failure behaviors of several materials, including metalmatrix and ceramic-matrix composites [35]. Particularly, the Weibull distribution has successfully described the delamination strength of 2G-HTS tapes [36]. In this study, the twoparameter Weibull distribution function was used, which is given as [37,38]:…”
Section: Electro-mechanical Behaviors Of the Tapes During Uniaxial Te...mentioning
confidence: 99%
“…In these works, effects of the cutting edges of the CCs was found to reduce the measured values of MDS [17][18][19]. Anvil configurations [20,21], loading speeds [22] and thickness of the silver layer [23] on the MDS measurement had little influence. Since the CC delamination is intimately related to the fracture and damage of ceramic, the threeparameter Weibull distribution based on the weakest link model often provide a proper statistics analysis [24,25].…”
Section: Introductionmentioning
confidence: 99%